2014
DOI: 10.1002/jrs.4622
|View full text |Cite
|
Sign up to set email alerts
|

Shedding light onto the spectra of lime: Raman and luminescence bands of CaO, Ca(OH)2 and CaCO3

Abstract: In microscopy studies of 19 th -century cement stone, we found free lime in the form of darkened spherical structures, as they were described in the literature already. When trying to determine their phase composition by Raman spectroscopy, we encountered contradictive assignments in literature spectra of the lime phases CaO, Ca(OH) 2 and CaCO 3 and observed strong spectral features that have been ignored or erroneously assigned so far. In this study we present Raman spectra of pure lime phases and of a natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 30 publications
9
75
0
1
Order By: Relevance
“…The high-frequency peak A 1g matches well the previously reported experimental and theoretical data, however, E 2g shows slight differences in peak position. For example, Padanyi et al [50] observed an E 2g peak at around 260 cm −1 while reports from Schmid et al [51] agrees well with our results. Accordingly, observed variations in the E 2g peak might be linked to differences in the phase or to hidden phases introduced during the growth.…”
Section: Vibrational Characteristics Of Monolayer Ca(oh)supporting
confidence: 93%
“…The high-frequency peak A 1g matches well the previously reported experimental and theoretical data, however, E 2g shows slight differences in peak position. For example, Padanyi et al [50] observed an E 2g peak at around 260 cm −1 while reports from Schmid et al [51] agrees well with our results. Accordingly, observed variations in the E 2g peak might be linked to differences in the phase or to hidden phases introduced during the growth.…”
Section: Vibrational Characteristics Of Monolayer Ca(oh)supporting
confidence: 93%
“…Schmid and Dariz [14] have suggested in their detailed report on spectral profile of lime materials excited by various laser lines that this phenomena occurs due to the generation of point defects by thermal and pressure conditions of lime burning, e.g. oxygen radical anions in the crystal lattice.…”
Section: Resultsmentioning
confidence: 98%
“…However, one can also observe laser-induced fluorescence features of strong intensity when using a near-infrared line, which may be mistakenly identified as Raman scattering. This effect has been observed during collection of NIR-Raman spectra by several groups studying different materials, mostly minerals and inorganic materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Dyer and co-workers have found fluorescence bands in cement materials [1], while others noticed their presence in materials containing calcium phosphate obtained synthetically and in the form of a biomaterial [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Note, the traces of SrO can be also detected by the presence of electronic transitions in the Raman spectrum arising from 4f ion interband luminescence emissions, excited by the laser beam (Fig. 3a) [31]. Such features are not observed on high dense ceramic pellets, free of any traces of second phases.…”
Section: Discussionmentioning
confidence: 95%